Digital immigrants' survival kit - Ebba Ossanilssonn (2021)
Societies today are more and more digital, and digital transformation has an impact on all sectors of our lives. Tasks that used to be done on paper are now done digitally, for example, government paperwork, tax returns, travel and booking systems, shopping, and other tasks. In order to understand and perform such tasks, the European Commission has launched the DigComp framework for citizens. During the pandemic COVID-19 this has been extremely visible, when everything went online, vulnerable groups became even more vulnerable due to lacking competencies, understanding, infrastructure, and even devices but maybe most of all habits, attitudes, and digital mindset. Digital competences need to be learned by users as it includes not only knowledge but also experiential competencies, skills, attitudes, and new mindsets. Without digital competencies, individuals will be excluded from society. Learning digital skills requires not only external motivation but also that users feel that they can engage and be more independent citizens. In a tech and digitally dominated environment, inclusion requires that persons feel able to use digital tools and resources wisely and safely for their own purposes. Many adults, although capable and integrated into other areas, need support to become competent and confident in using digital tools. The two-year Digital Immigrants Survival Kit (DISK, 2019-2022, 2019-1- PT01-KA204-060898) project aims to develop a Survival Kit to learn to overcome missing digital competencies of adults with a special focus on digital immigrants i.e., persons who are disadvantaged in society due to a lack of digital competences and to enable them to take an active role in the digital society. In this regard, the project team identified needs and competence profiles in potential participants and is constructing a set of 15 modules on a variety of topics related to daily life and digital competencies. The Survival Kit will use Flipped Learning 3.0 as a training approach and contribute to the development of an innovative self-evaluation tool: competence-based self-evaluation mandalas. Carefully designed transferability and implementation guides will support the flexible transfer of the results and outcomes to other European countries and its wide and open use, especially facilitated since DISK toolkit modules will be published as Open Educational Resources (OER). The consortium consists of 5 partners, 3 adult education organizations, a university, and a specialist in course quality and Open Educational Resources with complementary skills, experience, and approaches to adult education. The process of creation of the profiles and modules, as of the different elements such as the self-evaluation mandalas, and its challenges, are relevant to reflect on how, under the current social circumstances in the European Union, one can act effectively on developing digital competencies with older adults. Keywords: Adults, digitalization, digital immigrants, flipped learning, lifelong learning, mandala, selfevaluation, survival kit.